Perancangan Model Bisnis Usaha Washer Car Wash Tebet Berbasis Product-Service System (PSS) - Khansa Zhafira Fitri; Nanang Alamsyah; Mohammad Rachman Waluyo; Wendy Febrianty Mardhiyah (Journal of Optimization System and Ergonomy Implementation, 2025)
This study aims to design a business model for Washer Car Wash in Tebet using the Product-Service System (PSS) approach as a strategy to enhance competitiveness in the vehicle wash service industry. A descriptive qualitative method was employed through observations, questionnaires, and interviews with the business representative. The PSS analysis was conducted to identify the current business model (existing), desired development (desire), and the most feasible recommendation (eligible). The findings indicate that the current model operates as a pure service business, with development potential toward product related service and pay per service unit. Based on the quadrant analysis, product pooling emerges as the most feasible development, implemented through the concept of a “One Stop Care Hub” that integrates multiple automotive services within a single location. This recommendation is expected to enhance customer value, operational efficiency, and the competitive positioning of Washer Car Wash.